Sileno en la Égloga 6 de Virgilio: una captura en clave bucólica (Argos, 2024)
In Virgil”s Eclogue 6 (vv. 13-30) there is a scene in which two young men, Chromis and Mnasyllos, surprise the old satyr Silenus sleeping in a cave and, pretending a sort of a capture, they “compel” him to fulfill the promise to sing a song for them. Silenus is a mythological character with a long tradition, widely documented already from the 5th century B.C and characterized by his wisdom. The story of his capture by the order of King Midas, who wanted him to reveal his knowledge, is present in many different authors (e.g. Herodotus, Theopompus, Xenophon). Our article will examinate the construction of the character proposed by the Virgilian”s tale, which reiterates certain features from tradition but, at the same time, incorporates new elements. We will try to distinguish the meaning of those narrative components by which Virgil reappropriates of this figure in a bucolic key.
Keywords: Narration; Silenus; Eclogues; Virgil; Classical Antiquity